Interdisciplinary research has consistently lower funding success - Bromham, Lindell; Dinnage, Russell; Hua, Xia (Nature (London), 2016)
The degree of interdisciplinarity in research proposals negatively correlates with funding success across a wide range of research fields. The cost of interdisciplinarity In the recent past, governments and funding bodies have been keen to promote the merits of interdisciplinary research. But there is a widely held belief that such research faces higher barriers when it comes to applying for funding. Lindell Bromham et al . have mined data from the Australian Research Council to establish whether this gut feeling is based on reality. It is. They find that the degree of interdisciplinarity correlates negatively with funding success, irrespective of the research field. The authors go on to develop a metric — the interdisciplinary distance or IDD — that can be used to single out grant submissions that might be prone to this type of bias, so that their evaluation can be addressed proactively. Interdisciplinary research is widely considered a hothouse for innovation, and the only plausible approach to complex problems such as climate change 1 , 2 . One barrier to interdisciplinary research is the widespread perception that interdisciplinary projects are less likely to be funded than those with a narrower focus 3 , 4 . However, this commonly held belief has been difficult to evaluate objectively, partly because of lack of a comparable, quantitative measure of degree of interdisciplinarity that can be applied to funding application data 1 . Here we compare the degree to which research proposals span disparate fields by using a biodiversity metric that captures the relative representation of different fields (balance) and their degree of difference (disparity). The Australian Research Council’s Discovery Programme provides an ideal test case, because a single annual nationwide competitive grants scheme covers fundamental research in all disciplines, including arts, humanities and sciences. Using data on all 18,476 proposals submitted to the scheme over 5 consecutive years, including successful and unsuccessful applications, we show that the greater the degree of interdisciplinarity, the lower the probability of being funded. The negative impact of interdisciplinarity is significant even when number of collaborators, primary research field and type of institution are taken into account. This is the first broad-scale quantitative assessment of success rates of interdisciplinary research proposals. The interdisciplinary distance metric allows efficient evaluation of trends in research funding, and could be used to identify proposals that require assessment strategies appropriate to interdisciplinary research 5 .